Faktor-Faktor Yang Mempengaruhi Kunjungan Wisatawan Ke Candi Prambanan - SITI YUSNITHA, TITA; , Dra. Umrotun, M.Si (2017)
The increase of tourist visit at Prambanan Temple will affect the increase of regional income, so that can help the local community economy and can introduce culture and history. Some of the potential influence tourist visit to Prambanan Temple are like accessibility, facilities that provided by tour operational and the distance that not far from the city centre like Yogyakarta and Klaten City. The purpose of this research are : 1) Knowing the tourist characteristic that visit Prambanan Temple; 2) knowing the potential tourist attraction of Prambanan Temple; 3) knowing the dominant factor that attract tourist to pay a visit to Prambanan temple. This research using survey method with accidental purposive sampling,this technique sampling is intentionally or unexpectedly in accordance with the requirements of the sample required, this technique uses a variety of certain considerations such as the characteristics of tourists, among others, gender, age, occupation, and education, so samples not taken randomly but determined by researchers.Scoring technique using the assestment process between 1 to 3 at each research variables, tourist characteristic based on education, ocupation, age and tourist origin. Tourists who visit to Prambanan temple as seen from the status of ocupation based on interview, most of local tourist are students (37,33%), they are travel for holiday tor, while foreign tourist inculed in another category, they does not relate wit theoupation like self employed and company employees, they are include in freelance category that free to moving like travelling while waiting for the new jobs, with 52 % or 75 foureign tourist. Prambanan Temple has internal and external potential, with 13 score at grade levels based on quality on tourist attraction is at average class. Prambanan Temple has 3 main and the another component . External component with 22 score is at high class that affect the good accessibility and good facilities. Dominant factor that affect the tourist to visit Prambanan Temple because of the beauty temple, they can can also enjoy Sendratari Theater and screening film of Prambanan temple, Prambanan Museum, history of Prambanan Temple and some event that held at some spesific time.